Tracking Longitudinal Changes in Affect and Mindfulness Caused by Concentration and Loving-kindness Meditation with Hierarchical Linear Modeling - May, Christopher J.; Weyker, Jared R.; Spengel, Stephanie K.; Finkler, Lisa J.; Hendrix, Scott E. (Mindfulness, 2014)
We compared the relative effects of 5 weeks of either concentration or loving-kindness meditation (CM, LKM) on mindfulness (including two subscales—presence and acceptance) and affect using a multiple baseline ABA design. Hierarchical linear modeling (HLM) indicated that 48–71 % of the total variance was attributable to individual differences. While meditating, CM practitioners experienced progressive increases in mindfulness and acceptance, while LKM practitioners exhibited increases in mindfulness, presence, and positive affect. When practitioners ceased meditation, those in the CM condition declined in mindfulness, acceptance, and positive affect throughout the cessation period. Individuals in the LKM group showed a progressive decrease in presence and a singular drop in negative affect immediately following meditation. There was a dissociation between acceptance and presence, with CM influencing the former and LKM the latter. Because mindfulness and positive affect did not decrease after the meditation period for the LKM group, these results suggest that LKM may induce more enduring changes in these variables. However, while meditation-specific HLMs indicated differences between meditation types, a combined HLM with both meditation conditions showed no group differences in the meditation or cessation phases of the study. More substantial were individual differences in response to meditation; these point to the necessity of using either large sample sizes in group means testing for meditation research or techniques permitting individual-based analysis such as HLM and single-subject designs.